2018
DOI: 10.1111/jse.12298
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and evolutionary history of four closely related Aquilegia species revealed by 10 nuclear gene fragments

Abstract: The genus Aquilegia is emerging as the new model system for plant development, ecology, and evolution studies. Previous research showed that pollinator shift might drive the diversification of North American Aquilegia species, and natural selection on the length of petal nectar spur might play a crucial role. In this genus, A. ecalcarata Maxim. is the only taxon that has lost nectar spurs. Previous phylogenetic results indicated that A. ecalcarata, A. yabeana Kitag., A. oxysepala var. kansuensis Bruhl., and A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…kansuensis should be considered as a separate species rather than a variety. The phylogenetic tree shows that A. ecalcarata sequences were present on two different branches, providing further evidence to the previous report that A. ecalcarata is not monophyletic with a single origin and may have a complicated evolutionary history (Huang et al, 2018). In the future, to infer the phylogenetic relationships of rapidly evolving species within Aquilegia , we should collect more varieties and a greater number of species to construct the phylogeny.…”
Section: Discussionsupporting
confidence: 85%
“…kansuensis should be considered as a separate species rather than a variety. The phylogenetic tree shows that A. ecalcarata sequences were present on two different branches, providing further evidence to the previous report that A. ecalcarata is not monophyletic with a single origin and may have a complicated evolutionary history (Huang et al, 2018). In the future, to infer the phylogenetic relationships of rapidly evolving species within Aquilegia , we should collect more varieties and a greater number of species to construct the phylogeny.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, spur loss could have happened in a stepwise fashion, with mutations occurring first in these other loci affecting smaller aspects of spur morphology before mutations eventually occurred at POP. Studies focusing on population genetics in A. ecalcarata and its closest relatives may help clarify these scenarios (35). In either case, it is interesting to note that the major component of spur loss in A. ecalcarata appears to be caused by changes in POP expression, rather than function, perhaps because POP has pleiotropic effects on other traits such as leaf development.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the systematic molecular (Fior et al, ) and genetic diversity studies (Huang et al, ) showed that A . yabeana might be the ancestral species within the monophyletic clade, which consists of A .…”
Section: Discussionmentioning
confidence: 99%
“…kansuensis and one population similar to A . rockii (Huang et al, ), indicating the genetic differences within A. ecalcarata and the possible multiple origination of the spurless status. The present morphological study showed that, morphologically, all populations of A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation